Metformin and pancreatic cancer survival: Real effect or immortal time bias?. Issue 7 (25th March 2019) - Wei, Min; Liu, Yu; Bi, Yongyi; Zhang, Zhi‐Jiang
Abstract : High heterogeneity has been reported among cohort studies investigating the association between metformin and pancreatic cancer survival. Immortal time bias may be one importance source of heterogeneity, as it is widely present in previous cohort studies and may severely impair the validity. Our study aimed to examine whether metformin therapy improves pancreatic cancer survival, and to assess the impact of immortal time bias on the effect estimation of metformin in cohort studies. PubMed, EMbase and SciVerse Scopus were searched. Pooled relative risks (RRs) were derived using a random‐effects model. Pooled RR from the six studies without immortal time bias showed no association between metformin and mortality in pancreatic cancer patients (RR 0.93, 95% CI 0.82, 1.05; p  = 0.22 and I 2 = 75%). In contrast, pooled RR from the nine studies with immortal time bias showed a reduction of 24% in mortality associated with metformin (RR 0.76, 95% CI 0.69, 0.84; p  < 0.001 and I 2 = 1%). From a meta‐regression model, existence of immortal time bias was associated with a reduction of 18% in the effect estimate of metformin on pancreatic cancer survival (ratio of RR 0.82, 95% CI 0.70, 0.96; p  = 0.02). In conclusions, cumulative evidence from cohort studies does not support a beneficial effect of metformin on pancreatic cancer survival. The association between metformin and pancreatic cancer survival has been greatly exaggerated in previous cohort studies due to the wide existence of immortal time bias. More rigorous designs and statistical methods are needed to account for immortal time bias. Abstract : What's new? Metformin is a first‐line drug in the management of type 2 diabetes. More recently, metformin has also been suggested to prolong survival for cancer patients. However, high heterogeneity has been reported among cohort studies investigating pancreatic cancer survival, possibly due to immortal time bias. Here, the authors found that the cumulative evidence from cohort studies does not support a beneficial effect of metformin on pancreatic cancer survival. The association between metformin and pancreatic cancer survival has been greatly exaggerated due to the wide existence of immortal time bias in cohort studies, calling for more rigorous designs and statistical methods.